Zoonyms in the fi gurative space of the language: Metaphor, comparison, phraseological unit - Kosinets, Sergey Borisovich (Известия Саратовского университета. Новая серия. Серия Филология: Журналистика, 2022)
This article discusses linguistic units which actualize the fi gurative potential of zoonyms (animalisms, animal names) – metaphors, comparisons, phraseological units. The purpose of this research is to establish the lexical and semantic features of the units included in the fi gurative fi eld of zoonyms. The nuclear zone of the fi eld includes the names of animals, birds, fi sh, insects, spiders and microorganisms; the circumnuclear zone contains the names of prehistoric animals, mythical and fabulous creatures; the peripheral zone includes the names of animal dwellings, premises for their keeping and breeding, names of objects for catching animals and restricting their movements, actions, designations of sounds made by animals, their movements. The analysis of the material made it possible to establish that in the overwhelming majority of cases, zoonyms in their fi gurative use serve to characterize a person (his appearance, character traits, behavioral characteristics, social status). Animalistic metaphor expands its space by means of derivative vocabulary, which includes words that acquire the meaning of the derivational base, derivatives with comparative semantics and word-formation metaphors. Constituting the core of the fi gurative fi eld, animalistic metaphors, however, have less fi gurative potential than comparisons, since they name an object, feature or action directly, actualizing certain semes. Zoonyms usually have one or two metaphorical meanings, less often three. Comparisons, in many cases, point to very diff erent aspects of the compared objects, so they are in many cases occasional.